The impact of seeds provenance and nursery production method on Austrian pine (Pinus nigra Arn.) seedlings quality - Vladan Ivetić (Annals of Forest Research, 2013)
The influence of seed provenances and seedling production methodson quality of one and two years old seedlings of Austrian pine wereinvestigated. Seeds from three provenances of Austrian pine (Goč, Studenica and Šargan) were used for seedlings production, combined with three production methods: (i) the modified seedbeds (bare-root), (ii) the container type Plantagrah II and (iii) the container type Gočko. Provenance, as well as the combined influence of provenance and production method had minimal influence on the variability of one and two years old Austrian pine seedlings. Nevertheless, the production method had the highest influence. The production system, besides its importance in nursery, will have a high influence on seedlings growth during the first year after planting. Considering the results of this study (e.g. the highest values of the diameter, number of lateral roots, shoot and root dry weight, and quality index and the lowest value of SQ and satisfactory value of S:R), we can conclude that the seedlings produced in container type Gočko led to the highestseedlings quality, recommended especially for afforestation on hard sites.